2013
DOI: 10.1007/s11664-013-2890-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Beam Epitaxial Growth and Properties of Bi2Se3 Topological Insulator Layers on Different Substrate Surfaces

Abstract: Growth of high-quality Bi 2 Se 3 films is crucial not only for study of topological insulators but also for manufacture of technologically important materials. We report a study of the heteroepitaxy of single-crystal Bi 2 Se 3 thin films grown on GaAs and InP substrates by use of molecular beam epitaxy. Surface topography, crystal structure, and electrical transport properties of these Bi 2 Se 3 epitaxial films are indicative of highly c-axis oriented films with atomically sharp interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…The roughness of the sample is found to be 2.0 nm which is slightly higher than the roughness value analyzed from XRR measurements. This value of roughness is comparable to other Bi 2 Se 3 thin films prepared by MBE on GaAs (100) substrate . In order to study the chemical composition of the Bi 2 Se 3 thin film EDX was performed on the Bi 2 Se 3 thin film and the spectra is shown in Figure (d).…”
Section: Parameters Used To Get the Best Fit Of The Xrr Data For The supporting
confidence: 87%
“…The roughness of the sample is found to be 2.0 nm which is slightly higher than the roughness value analyzed from XRR measurements. This value of roughness is comparable to other Bi 2 Se 3 thin films prepared by MBE on GaAs (100) substrate . In order to study the chemical composition of the Bi 2 Se 3 thin film EDX was performed on the Bi 2 Se 3 thin film and the spectra is shown in Figure (d).…”
Section: Parameters Used To Get the Best Fit Of The Xrr Data For The supporting
confidence: 87%
“…Adjacent Te layers are weakly bonded across the van der Waals gap. Several studies have reported the growth of high‐quality, single crystalline thin films by molecular beam epitaxy (MBE) on single‐crystalline substrates, for example, Si, Al 2 O 3 , GaAs, and lattice‐matched InP to name a few, as well as amorphous SiO 2 /Si for back‐gated electrical transport measurements …”
Section: Growth and Structural Properties Of Re Doped (Bisb)2(sete)mentioning
confidence: 99%
“…The surface morphology, RMS roughness and size of the triangular domains are comparable to films grown on sapphire by MBE. 9 However, the lowest electron concentration obtained (~6.7x10 19 cm -3 ) results in a sheet carrier concentration of 2.2x10 14 cm -2 which is an order of magnitude higher than that reported for Bi 2 Se 3 films of comparable thickness grown by MBE 10,11 or hybrid physical-chemical vapor deposition (HPCVD) 12 which exhibit sheet carrier concentrations in the range of 0.6-3.0x10 13 cm -3 . This difference suggests that the Se/Bi ratio obtainable by MOCVD using DMSe and TMBi precursors is not sufficiently high to reduce the Se vacancy concentration in the layers.…”
Section: Se/bi Ratiomentioning
confidence: 65%